Batak Music Performance Management in The Toba Nauli Music Group Semarang (Universitas Negeri Semarang, 2023)
Toba Nauli is a group with a typical traditional genre of the Batak tribe with a unique way of managing the group and performing differently from other groups in general. Player substitutions happen at every event. For 8 years, Toba Nauli Music Group has been in the business of providing music services, especially Batak music. So, the question in this phenomenon is what form of management and how can the management function be applied to Toba Nauli Music Group? This study uses a qualitative descriptive method to analyze the management forms and functions of the Toba Nauli musical group and some data obtained through documentary research, observation, interviews, and documents. Data analysis techniques are performed by collecting data, presenting data, reducing data and drawing conclusions, and then checking the validity of the data by Triangulation method.The research results show that Toba Nauli Music Group has a management form, namely (1) the legal basis including the form of organizational structure, management structure, management policy, and it turns out that they have not prepared Drafting the Group Charter (AD) and Internal Regulations (ART). Music Toba Nauli; (2) Management functions include planning, organizing, monitoring, and targeting. It can be concluded that Toba Nauli Music Group has a qualified performing arts and organization management system even though there is no written AD/ART and can perform all possible management functions. maintains existence to this day.